Olive oil adulteration and energy efficiency: analytical innovations and sustainable perspectives - an integrative review - Pereira dos Santos, Maria de Fátima; Alves de Souza, Felipe Ravelly; de Araujo Vicente, Maristela (Latin American Journal of Energy Research, 2025)
Olive oil adulteration represents a growing challenge to product authenticity, food safety, and sustainability. This integrative review analyzed 18 studies published between 2023 and 2025, selected according to PRISMA criteria, focusing on analytical methods applied to fraud detection and their relationship with energy efficiency. Optical, magnetic, chromatographic, and multisensory techniques were evaluated based on sensitivity, energy consumption, waste generation, automation, and equipment life cycle. The NIR and TD‑NMR methods and the multisensor system were the most energy-efficient according to the parameters analyzed, achieving accuracies above 90% and detection limits between 2% and 5%. Conventional techniques, while accurate, require more infrastructure and higher energy input and generate chemical waste. Integration with artificial intelligence was recurrent, enhancing the robustness of predictive models. Despite progress, gaps remain, such as reliance on complex laboratories, the need for industrial validation, and the limited availability of portable devices with high precision. Considering these limitations, future perspectives point to the development of miniaturized sensors and autonomous analytical systems capable of performing local data processing and enabling rapid, accurate, energy-efficient, and sustainable analyses across various production and regulatory contexts.
Keywords: olive oil; adulteration; energy efficiency; sustainability; analytical methods.